Lifetime passes - Blas, Terry (Abrams ComicArts Surely, 2021)
"In this darkly comedic young adult graphic novel, a group of teens starts a program to bring senior citizens to a local theme park to take advantage of the unofficial park policy: If someone dies on the property, the rest of their party is given lifetime passes!"--Provided by publisher.